Floral Richness and Ecotourism Potential of Mundhum Trekking Trail in Eastern Nepal - Tiwari, Achyut; Bidari, Aashish; Rajbanshi, Shawan Kumar; Rai, Ramesh Kumar (Banko Janakari, 2026)
The Mundhum Trekking Trail (MTT) is a newly revived cultural trail in eastern Nepal, enriching traditional biocultural diversity. MTT shares elevation up to 4165 meters (viewpoint of Silchung Peak) from sea level and encompasses various lakes and mountains with high cultural values. Among them Salpa Pokhari and Silichung Peak (4,155 m asl) are key places. In this communication, we have reviewed the history and the initiatives undertaken to revive this trail, enumerated flowering plants and biocultural diversity and analyzed the ecotourism potentiality of this trail. We reported 264 species of angiosperms, belonging to 84 families and 190 genera, with the maximum number of species and genera belonging to Poaceae followed by Asteraceae. Further, we identified the culturally important plant and animal species used by Kirati people along the trail. Our results indicate that the newly revived historical trail has huge potential both as a cultural and an ecotourism trail. Besides, there has already been a surge of visitors in recent years, there is equally an urgent need to conserve the rich biocultural diversity along the trail to develop and promote it as purely a cultural ecotourism trail.